IMPACT OF CONSUMER BEHAVIOR BASED ON STORE ATMOSPHERICS - Dr Balagouda Patil; Dr. Guru Basava Aradhya S; Sateesh Kumar TK; B Sampath Kumar; M Shiva Shankar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
With advent of new and novel competition in retail sector prompt for exploring new elements in influencing the customer buying behavior. The larger retail brands are embarking on those factors to boost footfall and turn that traffic into sales. Purpose: The study aimed to look into the effect of store atmosphere on consumer buying behavior in Bengaluru retail stores. Examining the Strategies for retailers to boost store atmospheres and to distinguish a store’s appearance from that of its rivals, causing customers to spend more time and money and return to that store. Methodology: Current study uses is causal and quantitative approach, wherein the primary data was obtained and analyzed statistically from customers in Bengaluru This study examines the effect of atmospheric variables such as crowd density, store floor space, and product assortment on consumer buying behavior. Non-random convenience sampling was used to select sample respondents, and data was collected using a questionnaire that used the Likert Scale to quantify responses. Marketing and Theoretical implication: The store ambience viz., lighting and music pave the way for more appealing to customer visit. The store need to have crown management facility and other hedonic competence to convert to sales. The inference would be for better human and other elements certainly influence the customer buying behavior in retail stores.